Beliefs in social inclusion: Invariance in associations among hope, dysfunctional attitudes, and social inclusion across adolescence and young adulthood. (19th September 2017) - Berry, Clio; Greenwood, Kathryn
Abstract: Social disability in youth is an important precursor of long-term social and mental health problems. Social inclusion is a key policy driver and fits well within a new paradigm of health and well-being rather than illness-oriented services, yet little is known about social inclusion and its facilitators for "healthy" young people. We present a novel exploratory structural analysis of social inclusion using measures from 387 14- to 36-year-olds. Our model represents social inclusion as comprising social activity and community belonging, with both domains predicted by hopeful and dysfunctional self-beliefs but hopefulness more uniquely predicting social inclusion in adolescence. We conclude that social inclusion can be modeled for meaningful comparison across spectra of development, mental health, and functioning.